Congenital Cytomegalovirus Infection Epidemiology, Diagnosis, Therapy - Baumann, Gabriele; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2011)
Congenital cytomegalovirus (CMV) infection is the most common intrauterine transmitted viral infection, with a tremendous impact on fetuses and newborns. In this book the history of this disease, its pathophysiological background, epidemiology and symptoms, as well as diagnostic and therapeutic strategies, will be discussed. Since economic aspects are gaining more and more importance in health politics, one chapter is dedicated to this issue in the context of congenital CMV infection. The content is based on the latest scientific findings and written in an understandable manner, allowing persons not working in the field of congenital CMV to also profit from it. Thus, this book is of interest for medical doctors, nurses, midwives, economists, but also for men and women who want to inform themselves about this topic.
Keywords: Gynecology .; Medical microbiology; Infectious diseases; Public health; Health promotion; Gynecology; Medical Microbiology; Infectious Diseases; Public Health; Health Promotion and Disease Prevention